OPTIMALISASI KINERJA UMKM MELALUI PEMANFAATAN SOFTWARE AKUNTANSI DAN FINTECH PAYMENT GATEWAY - Saputro, Ilham Fajar Eko; Kamaluddin, Nurhadi Kamaluddin (Jurnal Sistem Informasi Akuntansi (JASIKA), 2024)
The purpose of this study was to examine the usefulness of financial technology such as payment getway and the role of mobile-based accounting software on improving the performance of MSMEs. The population of this research is MSMEs in Central Java. The sample of this research is 100 MSMEs in the food and beverage sector, with a sampling method that is purposive sampling. This type of research is quantitative research with data collection using a questionnaire. The data analysis technique used is Multiple Linear Regression Analysis using software (Statistical Product and Service Solution) SPSS version 25.0. The results of this study indicate that the fintech payment getway has a significant positive effect on the performance of MSMEs, mobile-based accounting software has a significant positive effect on the performance of MSMEs. The findings of this research provide benefits for MSME actors in improving their business performance so that they pay attention to the digitalization aspect of MSMEs